EVALUASI EFEKTIVITAS PENGGUNAAN MOBILE JKN DALAM PELAYANAN PASIEN RAWAT JALAN DI RSUD HAJJAH ANDI DEPU KABUPATEN POLEWALI MANDAR - Putri, Andi Masyita; Gobel, Fatmah Afrianty; Rusydi, Arni Rizqiani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
The digital transformation of health services through the Mobile Jaminan Kesehatan Nasional (JKN) application aims to improve administrative efficiency, reduce waiting times, and enhance patient satisfaction. However, its implementation in regional hospitals still faces challenges related to system integration, infrastructure readiness, and users’ digital literacy. This study aimed to analyze the effectiveness of Mobile JKN usage in outpatient services at RSUD Hajjah Andi Depu, Polewali Mandar Regency. A qualitative case study design was employed using the Donabedian framework (structure–process–outcome). Data were collected through non-participant observation, in-depth interviews, and document review. The results indicated that Mobile JKN improved administrative efficiency and queue management for online users, yet the average waiting time remained above service standards due to unsynchronized online and manual queues, network instability, and limited digital literacy among some patients. In conclusion, Mobile JKN has the potential to enhance outpatient service effectiveness when supported by system integration, stable network infrastructure, clear service standard operating procedures, and digital literacy education.